Predictive value of peritoneal cancer index for survival in patients with mucinous peritoneal malignancies treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy: a single centre experience. (4th July 2018) - Brandl, Andreas; Weiss, Sascha; von Winterfeld, Moritz; Krannich, Alexander; Feist, Mathilde; Pratschke, Johann; Raue, Wieland; Rau, Beate
Abstract: Objectives: This study investigated the correlation between the peritoneal carcinomatosis index (PCI) and patient outcome depending on the tumour type. Background: Peritoneal surface malignancy (PSM) treatment depends on tumour type. Mucinous PSM (m-PSM) is associated with a better prognosis than non-mucinous PSM (nm-PSM). The PCI's predictive ability has not yet been evaluated. Methods: We analysed 123 patients with PSM treated with cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) between 2008 and 2015. The m-PSM group ( n  = 75) included patients with appendiceal cancer ( n  = 15), colorectal cancer ( n  = 21), or low-grade appendiceal mucinous neoplasm ( n  = 39); the nm-PSM group ( n  = 48) included patients with gastric ( n  = 18) or colorectal ( n  = 30) cancer. The PCI's predictive ability was evaluated by multiple Cox-proportional hazard regression analysis and Kaplan–Meier curves. Results: The 5-year survival and PCI were higher in m-PSM patients (67.0%; 20.5 ± 12.1) than in nm-PSM patients (32.6%; p  = 0.013; 8.9 ± 6.0; p  < 0.001). Colorectal nm-PSM patients with PCI ≥16 had a worse 2-year survival (25.0%) vs. patients with PCI <16 (79.1%; log rank = 0.009), but no significant effect was observed in patients with m-PSM (66.7% vs . 68.1%; p  = 0.935). Underlying disease (HR 5.666–16.240), BMI (HR 1.109), and PCI (HR 1.068) significantly influenced overall survival in all patients. Conclusions: PCI is prognostic in nm-PSM, but not in m-PSM. CRS and HIPEC may benefit not only patients with low PCI, but also those with high PCI and m-PSM.